PUBLIC EXPENDITURE ON EDUCATION IN INDIA: TRENDS AND IMPLICATIONS - Guleria, Navneet; Mittal, R.K.; Isha, Tejee; Goutam, Supriya (International Journal of Engineering Technologies and Management Research, 2025)
Public spending on education in India has risen sharply in recent decades, signaling transformative changes in the country’s educational system. This study presents a detailed analysis of budgetary allocations, focusing on the distribution of funds across various levels of education. It identifies and evaluates key trends in public education expenditure, considering factors such as demographic shifts, economic conditions, and government policies. By examining financial patterns over time, the study aims to illuminate the shifting priorities of the Indian government in the education sector. Policymakers, educators, and other stakeholders must comprehend these tendencies in order to allocate resources and design policies with knowledge. The study also explores the makeup of educational spending, concentrating on how money is distributed to important areas including curriculum improvement, teacher pay, infrastructure development, and technology integration. The purpose of this compositional analysis is to identify sectoral priorities and evaluate whether budgetary allotments support more general goals of enhancing educational results and access. Additionally, the study investigates how public funds are allocated to primary, secondary, and postsecondary education levels. A better grasp of the government’s dedication to meeting the varied educational demands of different age groups and academic stages can be gained by examining investment trends at these levels. All things considered, this study provides insightful information about the complex dynamics of Indian public spending on education. It offers crucial direction for developing policies meant to improve the caliber, accessibility, and inclusivity of education in the nation by offering a thorough examination of trends, composition, and allocations.